Adaptation of the Cardiovascular Disease-Related Health Beliefs Scale to Turkish in Turkish Patients with Type 2 Diabetes; Validity and Reliability - Gülten Karahan Okuroglu; Nadire Ercan Toptaner (Hemşirelikte Araştırma Geliştirme Derneği, 2018)
Objective: The aim of the study is to define the validity and reliability of the Turkish version of Health Beliefs Related to Cardiovascular Disease Scale for individuals with type 2 diabetes. Methods: The study was conducted in methodological type. The study group was composed of 278 individuals with type 2 diabetes. The data were collected by Information form and Health Beliefs Related to Cardiovascular Disease Scale. The structural validity of the scale was evaluated by exploratory and confirmatory factor analysis. In the context of reliability analyses, Cronbach's alpha, the item-total score correlation, and the test-retest methods were used. Results: It was found that the four-factor structure explained 51% of total variance and that item loads ranged between .07 and .81. According to the results of confirmatory factor analysis, the two-factor structure of the scale was found to be better than the four-factor version in terms of fit indices X2/df=4.63, CFI=.94, RMSA=.12 .10-.13 , SRMR=.15 . While Cronbach's Alpha value was 0.69 for the whole scale. Positive and high level correlations were found in consequence of test-retest r= .724; p